Conflicting and harmonious sibling relationships of children and adolescent siblings of children with autism spectrum disorder. (11th November 2020) - Guidotti, Laura; Musetti, Alessandro; Barbieri, Gian Luca; Ballocchi, Ilenia; Corsano, Paola
Abstract: Background: The presence of a child with autism spectrum disorder (ASD) could have a strong psychological and emotional impact on typical development (TD) siblings, with different ways of adjustment and perception of fraternal relationships. In this study, we aimed to investigate the experience of the TD siblings of children with ASD, combining both quantitative and qualitative methodologies. Method: An explanatory sequential design was employed. Forty‐four TD siblings of children with ASD, aged 6 to 17 years old, participated in the study. Each participant completed the Sibling Relationship Inventory that investigated warmth, rivalry and conflict in sibling relationships. Moreover, in order to thoroughly evaluate the participants' perception of their sibling relationship, they were asked to draw themselves with their sibling with ASD in a condition of harmony and conflict. The drawings were collected and coded using the well‐validated Pictorial Assessment of Interpersonal Relationships. Quantitative and qualitative analyses were conducted. Results: In general, TD siblings showed affection for their siblings with ASD. However, males showed more conflict than females. Quantitative analyses of the drawings showed high levels of similarity between the siblings, despite the disability. In drawings, greater cohesion emerged in conditions of harmony and greater distancing in situations of conflict. Content analysis of the drawings showed that the conflict is represented mainly at home and the siblings often show opposite emotions, with TD siblings experiencing negative emotions. Moreover, adolescent TD siblings displayed more annoyance, shame and embarrassment than child TD siblings. Conclusions: It is important to combine quantitative and qualitative tools to understand the experience of TD siblings in detail. In particular, drawing is a useful tool for providing quantitative and qualitative information, supplying rich and detailed information that can be well integrated with the results coming from quantitative tools.